Peran Modal Sosial Dan Kur Terhadap Pengembangan Ikm Berbasis Kearifan Lokal Dan Kesejahteraan Pelaku IKM Di Kota Denpasar - Yudiantara, I Gede; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
Small and Medium Industries are exotic sectors that play an important role in business competition. This study aims to analyze the role of social capital and the use of KUR on the development of local wisdom-based IKM and the welfare of IKM actors in Denpasar City. The data used is primary data by distributing questionnaires to 67 local-based IKM practitioners in Denpasar City. The analysis technique used is path analysis. The results showed that social capital and the use of KUR had a positive and significant effect on the development of local wisdom-based IKM. Social capital and the development of local wisdom based IKM have a positive and significant effect on the welfare of IKM actors while the use of KUR does not affect the welfare of IKM actors. The development of local wisdom-based IKM is a variable that mediates the influence of social capital and KUR on the welfare of IKM actors in Denpasar City. That is, when social capital and KUR can be used properly, wisely, and on target for business development, it can improve the welfare of local wisdom-based IKM actors in Denpasar City.